In Vitro Antiplasmodial Activity of Brucein A Semisynthetic Compounds - Priska Ernestina Tenda; Eti Nurwening Solikhah; Mahardika Agus Wijayanti (Tropical Medicine Journal, 2012)
Introduction: Brucein A has been known to have antiplasmodial activity. Some new compounds were synthesized to increase their antiplasmodial activity, i.e 3-benzoylbruceinA, 3-dimethyl sulphate bruceine A, 3-choro benzoyl brucein A, and 3-chloro acetyl bruceine A.However, their antiplasmodial activity have not studied yet.Objectives: To know the in vitro antiplasmodial activity of 3-benzoyl brucein A, 3-dimethyl sulphate bruceine A, 3-choro benzoyl brucein A, and 3-chloro acetyl bruceine A.Methods: Antiplasmodial activity was conducted by incubating FCR-3 strain of P. falciparum with 3- benzoyl brucein A, 3-dimethyl sulphate bruceine A, 3-choro benzoyl brucein A, and 3-chloro acetyl bruceine A in various concentrations for 72 hours. Parasitemia after incubation period of each compound was calculated by making a thin smear stained with 5% Giemsa.Results: Semisynthetic compounds of bruceine A have antiplasmodial activity in vitro with IC50 value were 2.648 ± 1.30 ng/mL for 3-benzoyl bruceine A, 1.098 ± 0.510 ng/mL for 3-dimethyl sulphate bruceine A, 50.246 ± 0.207 ng/mL for 3-chloro benzoyl bruceine A and 67.951 ± 11.517 ng/mL for 3- chloro acetyl brucein A. The IC50 value of Bruceine A as the lead compound was 3.87 ± 2.530 ng/mLConclusion: The 3-dimethyl sulphate bruceine A showed the highest antiplasmodial activity among 4 semisynthetic compounds of Bruceine A.Keywords:bruceineA, semisynthetic compound, Plasmodiumfalciparum, invitroantiplasmodial activity.